Collaborative Writing in an EFL Context - Sri Rejeki Murtiningsih (Universitas Muhammadiyah Yogyakarta, 2016)
Working collaboratively has been widely promoted in education. In the area of English language teaching and learning, working collaboratively can frequently be seen in speaking activities, in which students were assigned to practice speaking with their peers. Unfortunately, working collaboratively in writing is not as popular as in speaking. This study aims to explore the collabora- tive writing in an EFL context. As a part of a bigger study, the data were collected through out a semester and integrated with weekly meetings, which aimed to reach several objectives through a variety of activities, including group painting, individual writing, and collaborative writing. A total of 64 freshmen that were divided into two groups participated in the study. In the collaborative writing activity, students were instructed to do group painting and write a story written in groups based on their paintings. Each member of the group took turns to write the story, which cohesiveness and coherence should be given attention. Students were given freedom to choose their own topics for painting and writing to encourage them express their ideas. The data were gathered through class observation and students’ reflection that was submitted at the end of the semester as a part of class assessment. The observation revealed that students faced some challenges when performing the tasks. Time management, student interdependence, and types of writing were among the issues emerging in collaborative writing activities. From students’ reflection, it was found that while most students stated they enjoyed the activities, one student expressed that the collaboration did not work as well as she had expected.